Application of just-in-time principles to financial services - Μάνου, Όλγα (2015)
This thesis investigates the application of selected Lean Manufacturing concepts to Financial Service operations. First, it overviews the methodology of Just-in-Time in manufacturing applications with emphasis in the Quality at the Source and Cellular Organization techniques. Second, it discusses characteristics of the Financial Services Sector and distinguishing differences from manufacturing. Existing implementations of the JIT methodology to financial services are also presented. Finally, the thesis examines the results of applying the Just-in-Time techniques of Quality at the Source and Cellular Organization to financial services, using simulation experiments. The results reveal if these techniques applied to financial service operations with certain characteristics can increase significantly productivity, by reducing simultaneously cycle time and resource utilization